AUTOIMMUNE DIATHESIS END RHEUMATOID ARTHRITIS IN CHILDREN - Lola K. Rakhmanova; Akramjon M. Rakhmanov (Central Asian Journal of Medicine, 2022)
In this article, the authors reviewed the literature, as a result, it was revealed that the pathogenesis of autoimmune diathesis, rheumatoid arthritis and rheumatoid nephritis in children has a general immunopathological nature. However, autoimmune diathesis is an important risk factor for the onset and progression of rheumatoid arthritis and the subsequent development of renal amyloidosis based on immunopathological reactions in these patients.